2012
DOI: 10.3945/jn.111.149328
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of (n-3) Fatty Acids in Foods: Challenges and Opportunities,

Abstract: The health benefits of long-chain (n-3) PUFA have been widely reported in the literature. Despite the potential benefits, consumption of these fatty acids continues to fall below recommendations from various health and regulatory agencies. Incorporation of long-chain PUFA in foods represents a considerable challenge due to the increased risk of lipid oxidation resulting in the development of off-flavors and reduced shelf life. As a result, new sources of (n-3) fatty acids are needed that are more efficiently c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 16 publications
0
41
0
4
Order By: Relevance
“…Flaxseed oil is inexpensive and easily available; but due to its highly polyunsaturated nature (>75 %), it is extremely susceptible to oxidation in presence of oxygen, metal ions and at high temperatures, which leads to the production of toxic hydroperoxides and off-flavor compounds during processing conditions. It is reported that α-linolenic acid (ALA, C18:3, ω-3) is 20 times more susceptible to oxidation as compared to oleic acid (C18:1) (Decker et al 2012). All these factors limit its applications as cooking/frying oil as well as its fortification in foods.…”
Section: Introductionmentioning
confidence: 99%
“…Flaxseed oil is inexpensive and easily available; but due to its highly polyunsaturated nature (>75 %), it is extremely susceptible to oxidation in presence of oxygen, metal ions and at high temperatures, which leads to the production of toxic hydroperoxides and off-flavor compounds during processing conditions. It is reported that α-linolenic acid (ALA, C18:3, ω-3) is 20 times more susceptible to oxidation as compared to oleic acid (C18:1) (Decker et al 2012). All these factors limit its applications as cooking/frying oil as well as its fortification in foods.…”
Section: Introductionmentioning
confidence: 99%
“…However, as mentioned briefly in the previous section, the presence of double bonds may promote lipid oxidation due to their high reactivity and lower chemical stability and strength, 74 which strongly affects products containing a high -3 fatty acid content. Lipid oxidation in meat products is commonly measured by the thiobarbituric acid reactive substances (TBARS) method, with the principle based on the fact that the products of primary oxidation mainly consist of hydroperoxides, which are quickly broken wileyonlinelibrary.com/jsfa down into several substances reactive to the thiobarbituric acid, particularly carbonyls, with malondialdehyde the most important element.…”
Section: Lipid Oxidation In Meat Productsmentioning
confidence: 99%
“…73 The oxidative stability of -3-enriched foods is also impacted, since the product is more susceptible to lipid oxidation due to the double bonds in the -3 fatty acid molecule, rendering them more accessible to free radicals and oxygen reactive species, resulting in damage to the product's sensory properties. 74 It is worth noting that protein oxidation in foods is directly affected by lipid oxidation, since the products of lipid oxidation react with proteins leading to their subsequent oxidation, primarily causing changes in aroma and color. 75 The mechanisms of lipid oxidation and its effects on meat products are outlined below.…”
Section: Impact Of the Addition Of -3 Fatty Acids On The Oxidative Stmentioning
confidence: 99%
“…La industria farmacéutica y nutracéutica ha desarrollado alternativas para mejorar el consumo de aceites marinos (15). Estos aceites se pueden encapsular (cápsulas blandas, muy comunes) (15), microencapsular (16) e incluso nanoencapsular (17).…”
unclassified
“…Estos aceites se pueden encapsular (cápsulas blandas, muy comunes) (15), microencapsular (16) e incluso nanoencapsular (17). La encapsulación es la forma más habitual y organolépticamente menos compleja para aportar EPA + DHA, pero no es fácilmente aceptada por todos por el tamaño de las cápsulas (contienen hasta 3 gr de aceite), sobre todo por los más pequeños y los más ancianos.…”
unclassified